TOMATO BENEFITS IN REDUCING THE RISK OF PROSTAT CANCER - Kadek Wisnu Mataram; Ida Ayu Ika Wahyuniari (E-Jurnal Medika Udayana, 2013)
Consumption of fresh and processed tomato products is associated with reduced risk of prostate cancer. The emerging hypothesis is that lycopene, the primary red carotenoid in tomatoes, may be the principle phytochemical responsible for this reduction in risk. A number of potential mechanisms by which lycopene may act have emerged, including serving as an important in vivo antioxidant, enhancing cell-to-cell communication via increasing gap junctions between cells, and modulating cell-cycle progression. Although the effect of lycopene is biologically relevant, the tomato is also an excellent source of nutrients, including folate, vitamin C, and various other carotenoids and phytochemicals, such as polyphenols, which also may be associated with lower cancer risk. Tomatoes also contain significant quantities of potassium, as well as some vitamin A and vitamin E.